Ryanair and Spain: Air connectivity and tourism from the perspective of complex networks - Tatiana Iñiguez; Marta Plumed; María Pilar Latorre Martínez (Tourism & Management Studies)
This research presents an innovative exploratory study of connectivity in Spain through the analysis of the main low-cost air company in Europe, Ryanair, employing complex network theory techniques. Knowing the connectivity of each one of the airports that operate in Spain, we analyse the different characteristics of national and international tourist flows in the country. Our results show that the most important European tourist flow is from United Kingdom to the Spanish coast and that the diversification of flights at different airports in the country promotes the development of new tourist destinations which have thus experienced an increase in their number of visitors. We start a new line of research that can analyse different parameters of air connectivity and the implications for tourism.